Effect of Freezing Methods on the Physical and Chemical Properties and Protein Oxidation of Porcine Liver - Ge ZHANG; Juan YOU; Hong YANG (Shipin gongye ke-ji)
To address the quality deterioration of porcine liver during frozen storage, the impacts of different freezing methods on porcine liver were investigated, including −20 ℃ conventional air freezing (CAF), −80 ℃ refrigerator cryogenic freezing (RCF) and liquid nitrogen immersion freezing (LNF). The ice crystal microstructure, color, total volatile base nitrogen (TVB-N) value, thiobarbituric acid reactive substances (TBARs) value, carbonyl content, sulfhydryl and disulfide bond content and surface hydrophobicity of porcine liver were determined. The results showed that as the storage time was increased, the quality of porcine liver decreased and the degree of protein oxidation increased. Porcine liver from the RCF and LNF groups formed finer and more uniform ice crystals, which passed through the maximum ice crystal formation zone in less time than the CAF group (71.60% and 99.81%, respectively). In addition, the TVB-N and TBARs values in the LNF group decreased by 28.43% and 41.79% respectively after storage for 180 d compared to the CAF group. Furthermore, compared to the CAF group, the carbonyl content, disulfide bond content and surface hydrophobicity of proteins in the LNF group decreased by 38.88%, 6.77% and 21.04%, respectively, and the sulfhydryl content increased by 8.60%, indicating that the use of LNF could reduce the oxidation of porcine liver proteins significantly. The results suggested that by modifying the freezing method, the freezing rate was increased and the degree of damage caused by ice crystals to porcine liver cell tissues was reduced, effectively preventing the deterioration of porcine liver quality. The results of this investigation could provide technical support for the transportation and freezing of porcine liver.